The effect of obesity on intraocular pressure in nonglaucomatous eyes - Dr. Maryam Dhafer Shareef; Dr. Zainab Yessar mohammed hassan; Dr. Rusel Mohammed Salman; Dr. Ali Qais Abdulkafi (Zien Journals, 2023)
Some eye diseases like cataract, glaucoma, diabetic retinopathy, and age-related macular degeneration were reported to have potential relation to obesity. Obesity possesses an increased risk for both elevated intraocular pressure and systemic vascular abnormalities such as hypertension and arteriosclerosis.
Keywords: Obesity; intraocular pressure; body mass index